Intensitas Penggunaan Smartphone Sebelum Tidur dan Bedtime Procrastination Pada Mahasiswa - Aryani, Eka; Rindiani, Rindiani (TERAPUTIK: Jurnal Bimbingan dan Konseling, 2025)
Some students of the Faculty of Teacher Training and Education at Universitas Mercu Buana Yogyakarta often play smartphones before bed, so they have difficulty adhering to their sleep schedule, known as bedtime procrastination. This study aimed to examine the relationship between the intensity of smartphone use before bed and bedtime procrastination in students of the Faculty of Teacher Training and Education at Universitas Mercu Buana Yogyakarta. In this study, we employed a quantitative approach using a correlational method. The subjects of this study were students of the Faculty of Teacher Training and Education, Universitas Mercu Buana Yogyakarta, with a sample size of 222 students. The sampling technique used was simple random sampling. The data collection instrument was a questionnaire that included a smartphone usage intensity scale and a bedtime procrastination scale. Instrument validity uses construct validity by expert validators, and item validity tests using the correlation formula by comparing rcount with rtable. Reliability uses the Cronbach’s alpha formula. The intensity of smartphone use before bed had a reliability value of 0.878, and bedtime procrastination had a reliability value of 0.804. Data analysis was performed using simple correlation techniques with Spearman’s rank. The results showed that rcount was greater than rtable, namely 0.417>0.138, and a significance value of of <0.001, which means less than 0.05. This means that there was a significant positive correlation between the intensity of smartphone use before bedtime and bedtime procrastination. The X and Y variables have a degree of correlation of 0.417; therefore, they are included in the moderate relationship category